“The Germany kann me furchtbar leckn!”: Radio Essays that Take On the Ghosts of the Past (KULT_online, 2010)
Ansgar Warner's dissertation thesis throws light on a very special aspect of the political and cultural history of the early Federal Republic of Germany: the struggle of well-known authors Arno Schmidt and Wolfgang Koeppen against the lingering traditions of nationalism, fascism and militarism. Analysing six radio essays, Warner considers this genre to be a ‘meta-medium’ of collective remembrance which had a great deal to do with the shaping of West Germany’s public memory, and which eventually fostered the democratisation of West German society and its political culture. The study convincingly traces the political impulses of both authors and charts the radio essay as a literary genre; it lacks, however, the proper consideration of its ‘soundscape’ and medial relevance.